TERRA EDUCATION 2010 INTERNATIONAL SEMINAR: EDUCATION FOR EARTHEN ARCHITECTURE - Guillaud, Hubert; Achenza, Maddalena; Avrami, Erica; Correia, Mariana; Guerrero Baca, Luis Fernando; Houben, Hugo (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2012)
In the year 2010, from May 24th to May 29th, the National Superior School of Architecture of Grenoble (ENSAG), France, with the CRAterre-ENSAG Research Unit and the UNESCO Chair Earthen Architecture, organized an international seminar on education for earthen architecture. More than 40 university lecturers, researchers and experts in education, coming from Europe, Africa, America, Asia, representing the interface of numerous international, regional and national specialized networks (such as PROTERRA, UNESCO Chair, Cedterra, DachverbandLehm e.V, ASterre, TerraKorea), universities and faculties of architecture or engineering, research units, training centers, and NGOs, were invited. During six days, they shared their experiences, debated the state of the art in the ield, and developed a joint relection. This allowed envisioning the future development of higher education and research (didactics and pedagogy, PhD programs), and vocational training and actions aiming at promoting awareness for the general public regarding earthen architecture, its conservation and its contribution to sustainable development. Based on 22 presentations, prepared by 96 contributors, this collective relection was then developed within four thematic workshops, as follows:Workshop 1: Reviewing the types of higher-education and vocational-training curricula available, educational tools and learning methods;Workshop 2: Strategic directions for research and doctoral programs: what research priorities to develop in order to meet the expectations and needs of society?Workshop 3: Methods of evaluation and validation of skills learned; certiication of professional qualiications;Workshop 4: Dificulties, gaps and blockages/instances, and acceleration of education-development actions and specialized training in earthen construction and architecture.